Survivin Ser81 Plays An Important Role in PI3K/Akt/mTOR Signaling Pathway - Ferry Sandra (Molecular and Cellular Biomedical Sciences, 2018)
Background: Survivin, a member of the inhibitor of apoptosis protein family, has been associated with protection from cell apoptosis and regulation of mitosis. Phosphorylated-Survivin at Ser81 was reported to provide cytoprotection against tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) in L929 cells by inducing a backloop activation of phosphatidylinositol 3-kinase (PI3K). Therefore Akt as a possible substrate of PI3K was investigated.Methods: L929 cells were pretreated with/without 50 μM LY294002 or 10 μM Perifosine, and infected with viral particle of Survivin, anti sense of Survivin, Ser81Ala mutated Survivin or vector only. Cells were then harvested, lysed and subjected to immunoblot assay to detect Akt, phosphorylated Akt (Ser473), mammalian target of rapamycin (mTOR), phosphorylated-mTOR (Ser2448).Results: Survivin induced Akt and mTOR phosphorylations in a viral particle concentration dependent manner. Pretreatment of LY294002 or Perifosine prior to Survivin infection, attenuated Akt or mTOR phosphorylations, respectively. Low Akt or mTOR phosphorylations were observed when L929 cells were infected with Ser81Ala mutated Survivin.Conclusion: Ser81 phosphorylation site of Survivin played an important role in activating Survivin/PKA/PI3K/Akt/mTOR signaling pathway.Keywords: survivin, Ser81, Akt, mTOR, LY294002, perifosine